EVALUASI KINERJA OPERATOR SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA (SIMAK-BMN) DI POLDA DIY - Dewi Indarwati; Eka Ambara Harci Putranta (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to 1) Identify the inhibiting factors of the performance of the Management Information and Accounting Information System for State Property (SIMAK-BMN) in POLDA DIY. 2) Formulate efforts to improve the performance of the Management Information System and Accounting for State Property (SIMAK-BMN) in DIY Regional Police. This research use desciptive qualitative approach. Data were collected using a questionnaire against 71 respondents. The data analysis technique used is Descriptive Statistics analysis. The results showed that the performance of the Management and Accounting Information System Operator of State Property (SIMAK-BMN) in DIY POLDA was not optimal because SIMAK BMN operators did not understand the meaning of management information systems and accounting for state property and SIMAK regulations lacked mastery about the application of SIMAK BMN. Efforts to improve the quality of the Management Information and Accounting Information System for State Property (SIMAK-BMN) IN DIY POLDA is to provide understanding to SIMAK BMN operators and assistance to SIMAK operators. Efforts to improve the performance of Operators of the Management and Accounting Information System for State-Owned Goods (SIMAK-BMN) in POLDA DIY is a transparent performance evaluation system, fulfilling the rights of operators of the Management and Accounting Information System of State-Owned Goods, reward and punishment for the operator of Management and Accounting Information Systems The state, career path, training and training, are made conducive physical and non-physical work environment.